Empowerment in EU energy law: connecting legal and sustainability transition perspectives - Pepijn Quast; Wouter Boon; Sanne Akerboom (Environmental Innovation and Societal Transitions, 2027)

An elephant in the glasshouse? Trade-offs between acceleration and transformation in COVID-19 vaccine innovation policies - Linda van de Burgwal; Tom van der Valk; Hannes Kempter; Manuel Gadau; David Stubbs; Wouter Boon (Environmental Innovation and Societal Transitions, 2023)

Replacing meat, an easy feat? The role of strategic categorizing in the rise of meat substitutes - Marjolein J. Hoogstraaten; Koen Frenken; Taneli Vaskelainen; Wouter P.C. Boon (Environmental Innovation and Societal Transitions, 2023)

Knowledge co-production in protective spaces: case studies of two climate adaptation projects - Wouter P. C. Boon; Laurens K. Hessels; Edwin Horlings (Regional Environmental Change, 2019)

Industrial Symbiosis Dynamics and the Problem of Equivalence: Proposal for a Comparative Framework - Frank Boons; Marian Chertow; Jooyoung Park; Wouter Spekkink; Han Shi (Journal of Industrial Ecology, 2017)
Summary Industrial symbiosis (IS), one of the founding notions within the field of industrial ecology, has diffused throughout significant parts of the world as a practice that can reduce the ecological impact of the industrial processes of groups of firms. In this article, we propose a fresh look at this research topic, building on the considerable advances that have been made in the last 15 years in understanding how IS comes about. We propose a conceptual and theoretical framework for taking on the challenge of comparative analysis at a global level. This requires developing an approach to address a solution to the problem of equivalence: the difficulty of comparing instances of IS across different institutional contexts. The proposed framework emphasizes IS as a process and attempts to address the obstacles to comparative study by (1) identifying terminology to examine IS variants, (2) providing a typology of IS dynamics, and (3) formulating key research questions to illuminate a way forward. In developing our argument, we build on the collective experiences of collaborative research efforts in North America, Europe, and Asia as evidenced in recent overviews of the literature.

An analysis of marketing authorisation applications via the mutual recognition and decentralised procedures in Europe - Hans C. Ebbers; Joris Langedijk; Jacoline C. Bouvy; Jarno Hoekman; Wouter P. C. Boon; Jean Philippe de Jong; Marie L. De Bruin (European Journal of Clinical Pharmacology, 2015)

A Process Perspective on Industrial Symbiosis - Frank Boons; Wouter Spekkink; Wenting Jiao (Journal of Industrial Ecology, 2014)
Summary It has been long recognized in the conceptual literature that industrial symbiosis requires a perspective that focuses on long‐term evolution. This has not yet been matched by adopting an adequate process‐oriented research methodology. This article provides the underpinnings for such a methodology, presents a developed methodology, event sequence analysis, and shows its added value through a set of research questions and an empirical example. It shows how the process perspective leads to asking new research questions as well as the uncovering of new insights about the emergence, evolution, and dissolution of symbiotic relationships and the institutional capacity required to build such relationships.

Levels of Institutional Capacity and Actor Expectations about Industrial Symbiosis - Frank Boons; Wouter Spekkink (Journal of Industrial Ecology, 2012)
Summary One assumption underlying the work on industrial symbiosis (IS) is that certain social conditions must be fulfilled in order for firms to develop symbiotic linkages. In this article we add depth to this insight by using institutional capacity as an underlying concept for these conditions, and we propose that such capacity influences IS by altering the opportunity set of actors. We then test the assumption on a dataset of 233 projects aiming to develop eco‐industrial parks. We find that the link between institutional capacity and the opportunities for symbiotic linkages perceived by actors is not always present and is more complicated than has been recognized thus far. We discuss potential alternative ways in which institutional capacity might influence IS and present ideas for future research to shed light on this important relationship.

CLSM as Quantitative Method to Determine the Size of Drug Crystals in a Solid Dispersion - Hans de Waard; Martin J. T. Hessels; Maarten Boon; Klaas A. Sjollema; Wouter L. J. Hinrichs; Anko C. Eissens; Henderik W. Frijlink (Pharmaceutical Research, 2011)

High protein diet induces pericentral glutamate dehydrogenase and ornithine aminotransferase to provide sufficient glutamate for pericentral detoxification of ammonia in rat liver lobules - Louis Boon; Willie J. C. Geerts; A. Jonker; Wouter H. Lamers; Cornelis J. F. Van Noorden (Histochemistry and Cell Biology, 1999)